2018
DOI: 10.1109/lmwc.2018.2845947
|View full text |Cite
|
Sign up to set email alerts
|

A Doubly Orthogonal Matching Pursuit Algorithm for Sparse Predistortion of Power Amplifiers

Abstract: This letter presents a new method for the digital predistortion of power amplifiers (PAs) based on sparse behavioral models. The Gram-Schmidt orthogonalization is synergistically integrated into the orthogonal matching pursuit algorithm to decorrelate the selected model regressors against the components still to be selected. Experiments conducted on a test bench based on a GaN PA driven by a 15-MHz orthogonal frequency division multiplexing signal were conducted in order to validate the algorithm. Experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 8 publications
0
27
0
Order By: Relevance
“…Considering that the matrices defined earlier are sized by the number of model components, which is generally much lower than the number of samples in the regressors, the resulting algorithm shows a computational complexity that is fixed for every iteration compared with that of the previous versions of the algorithm [11], [13], [21] that required increasing computations with the number of selected coefficients. Sections III-A-III-F overview the steps of this contribution.…”
Section: Reduced-complexity Dompmentioning
confidence: 99%
See 3 more Smart Citations
“…Considering that the matrices defined earlier are sized by the number of model components, which is generally much lower than the number of samples in the regressors, the resulting algorithm shows a computational complexity that is fixed for every iteration compared with that of the previous versions of the algorithm [11], [13], [21] that required increasing computations with the number of selected coefficients. Sections III-A-III-F overview the steps of this contribution.…”
Section: Reduced-complexity Dompmentioning
confidence: 99%
“…where O stands for the quantity of real-number multiplications at iteration k. It can be observed that the original DOMP [11] exhibits a complexity dominated by the cubic of the iteration number that results of the m × k pseudoinverse calculation at each iteration; in the SSPI DOMP [21], this relationship is reduced to quadratic dependence, and in the novel RC-DOMP, there is no dependence with the iteration number. Considering that m/n is the number of samples per regressor, it is straightforward to conclude that the RC-DOMP outperforms the rest of the algorithms under comparison.…”
Section: Complexity Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The orthogonal matching pursuit (OMP) was first applied to PA DPD in [16], followed by a reduced-complexity version of the algorithm in [17]. To overcome the high correlation that appears in Volterra series, the doubly OMP (DOMP) was designed [18] as well as its low-complexity variant [19].…”
Section: Introductionmentioning
confidence: 99%